On compulsive talkers - Kirkpatrick, JR (Springer Nature, 2024)
This paper reevaluates Kaplan’s (Themes from Kaplan, Oxford University Press, Oxford, pp 481–563, 1989b) infamous ‘compulsive talker’ objection to Reichenbach’s (Elements of symbolic logic, AQ1 Macmillan, New York, 1947 ) token-reflexive theory of indexicals. It argues that Kaplan’s objection depends on the modal status of Reichenbachian tokens. On one interpretation, Kaplan’s objection stands. But on another, equally plausible interpretation, the following points hold: (i) Reichenbach’s theory effectively preempts contemporary discussion of rigid definite descriptions, (ii) Kaplan’s own analysis of indexicals in terms of dthat-terms comes extremely close to Reichenbach’s own analysis, and (iii) Kaplan’s ‘compulsive talker’ objection should be rejected.